The Impact of Open-Access Status on Journal Indices: Respiratory and Pulmonology Journals - AlRyalat, Saif A.; Abu Nassar, Anas; Tamimi, Faris; Al-Fraihat, Esraa; Assaf, Lama; Ghareeb, Razan; Masoudi, Mahmoud; Al-Essa, Mohammad (Current Respiratory Medicine Reviews, 2019)
Background: Open access (OA) publishing is rapidly emerging in almost all disciplines, with variable intensity and effect on the discipline itself. The move toward OA is also observed in the field of respiratory and pulmonology, where both OA data repositories and OA journals are rapidly emerging. Objective: we aim to study the open-access status of respiratory and pulmonology journals and the impact of the open-access status on journal indices. Methods: We collected journal’s data from Scopus Source List on 1st of November 2018. We filtered the list for respiratory and pulmonology journals. Open Access Journals covered by Scopus are recognized as Open Access if the journal is listed in the Directory of Open Access Journals (DOAJ) and/or the Directory of Open Access Scholarly Resources (ROAD). For each journal, we used several metrics to measure its strength, and then we compared these metrics between OA and non- OA journals. Results: There were 125 respiratory and pulmonology journals, a number that has increased by 12.6% since 2011. Moreover, the percentage of OA journals has increased from 21.6% to 26.4% during the same period. Non-OA journals have significantly higher scholarly output (p= 0.033), but OA journals have significantly higher percentage of citation (p= 0.05). Conclusion: Publishing in OA journals will yield a higher citation percentage compared to non-OA journals. Although this should not be the only reason to publish in an OA journal, it is still an important factor to decide where to publish.
Keywords: Bibliometry